All Epiphyseal ACL Reconstruction in Skeletally Immature Patients Using Quadriceps Tendon Autograft - Sercan Yalcin MD; Jacob Maier MD; Paul Saluan MD (SAGE Publishing, 2022)
Background: The incidence of anterior cruciate ligament (ACL) tear in the skeletally immature pediatric population has been steadily increasing due to multiple factors, including multiple sports participation, year-round training, and the increase in the number of athletes. Reconstruction in these patients is challenging due to the open physes at the distal femur, proximal tibia, and tibial tuberosity apophysis. Violation of the physis can result in angular deformities or leg length discrepancies. Indications: To demonstrate steps of all epiphyseal ACL reconstruction in skeletally immature patients using quadriceps tendon autograft. Technique Description: After the patient is positioned, prepped, and draped, the quadriceps tendon autograft is harvested and prepared to be used as the autograft. Using the all-inside technique, femoral and tibial tunnels are created as all-epiphyseal to prevent violating the physes. The ends of the graft are then passed through the tunnels and fixed with an adjustable loop on the femur and a button on the tibia. Results: Although excellent clinical outcomes and a high return to sports rates have been reported after ACL reconstruction, the technique to be chosen is not clear yet. Discussion/Conclusion: Quadriceps tendon autograft provides an excellent alternative as a graft choice in skeletally immature patients.